شبلی نعمانی کی الفاروق اور غلام احمد پرویز کی تصنیف شاہ کارِ رسالت ﷺکا تقابلی مطالعہA Comparative Study of Shiblī’ No‘manī’s “al-Farooq: and Ghulam Ahmad Pervaiz’s “Shāhkār-e-Risālat” (Al-Qamar, 2021)
This  article presents a detail review of the books of two renowned scholars of Indo-Pak. In this aspect, this article provides a momentary comparison about the similarities and differences, qualities and components of these two books. First book is "Al-Farooq" written by Shiblī’ No‘manī, while "Shāhkār-e-Risālat" is the masterpiece of Ghulam Ahmad Pervaiz. Both these books describe the biographical work about the life of the second Caliph of Islam, Umar b. al-Khattab. Although, these two books are on the same topics and having almost same contents, facts and figures and some similarities but these books differ in their focus and style, with "Al-Farooq" taking a more straightforward and historical approach, while "Shahkar Risalat" is more critical and anticipated and projected target oriented in nature. However, both books share a common goal of providing readers with a deeper understanding of the life of the important figure of Islamic history. Additionally, both works aim to help readers gain insight into the historical and cultural context of early Islam, and the impact of his life had on the development of the Islamic civilization and its followers. In conclusion, both "Al-Farooq" and " Shāhkār-e-Risālat " are valuable resources for those interested in learning more about the early years of Islam and the life of Hazrat Umar.
Keywords: Shiblī’; “Al-Farooq; Pervaiz; “Shāhkār-e-Risālat”; Comparative Study